Comparative study of production control systems through simulation - (:unkn) unknown (My University, 2009)
The purpose of this chapter is to simulate pull, push and hybrid production control systems for a single line, multi-stage and continuous production process, which is aluminium casting, in order to compare their performances where the current production control system is push system. This chapter also provides an approach in constructing hybrid system by using TSP in minimizing total setup time to obtain optimal sequence of orders. © 2009 Springer Science+Business Media LLC.
Keywords: Hybrid system; Production control systems; Pull system; Push system; Simulation; Travelling salesman problem